(untitled) (Comparatismi, 2017)
In 1994 Semir Zeki’s neuro-aesthetics formalizes the interdisciplinary approach to aesthetic facts, linking scientifically the brain to creativity. Consequently, the history of art becomes a neuroarthistory of the human mind, defined as such in 2005 by the historian John Onians. Finding a universal code, based on the nervous system and able to decipher each visual preference and every stylistic shift is the aim of this new analytic attitude. The identification of both the contextual element on which the gaze is intensively and frequently set, bringing to perceptual choices’ neural changes, and the particular mind plasticity modulation, as the genetic basis of any local forma mentis, clarifies how the brain conditions form the artistic manner. For this type of exam, the historian needs to observe in the creator’s and consumer’s brain the workings of the major cortical resources, such as neural plasticity, the rewarding system, the sectoring of the visual system, the intrinsic functional connectivity and mirror neurons. The discovery of this variability of “brain behavior” is the basis of the style shifts and the first step towards the neurohistory of art. Therefore, the named neuro-historical art analysis develops a narration of the somatosensory perceptions of the world, expressed through the language of forms. The latter infers, with the certainty of scientific data, the historical awareness and the aesthetic interpretation, opening up a new dimension of art criticism.